Structural Foundations of Equity (Insaf) and Equilibrium (iᶜtidāl) in Hadith Criticism–A Methodological Study - Abdel Salam A. Abu Samha (مجلة كلية الشريعة والدراسات الإسلامية)
Objectives: This study explores the methodologies engaged by Hadith scholars to maintain fair judgement and equity (inṣāf) and equilibrium and moderation (iᶜtidāl) in their criticism—an endeavor that represents one of the most complex evaluative methodologies in determining the reliability of reports and their narrators. For Hadith criticism (taḥqīq), with its intricate epistemic tools and evaluative criteria, demands a rigorous commitment to objectivity and impartiality.